2017
DOI: 10.30704/http-www-jivs-net.324403
|View full text |Cite
|
Sign up to set email alerts
|

Inherited Diseases of Holstein Cattle: Story So Far in Turkey

Abstract: Inherited diseases are caused by recessive alleles proceed from increased inbreeding in Holstein cattle population. Bovine leucocyte adhesion deficiency (BLAD), deficiency of uridine monophosphate synthase enzyme (DUMPS), complex vertebral malformation (CVM), factor XI deficiency (FXID) and bovine citrulinaemia (BC) are the most frequent inherited diseases in Holstein cattle population. The prevalence for carriers of BLAD, DUMPS, CVM, FXID and BC diseases were reported highest in Denmark (21.5%), USA (1.2%), J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…It was also lower than that reported by previous Taiwanese studies, in which 409, 172 and 436 cattle from 4, 4 and 9 herds, respectively, with BY carrier frequencies of 8.56, 12.21 and 6.65%, respectively, were sampled (Liaw et al, 2015;2017;Lai et al, 2017). The variations in carrier prevalence were consistent with those found in a study in Turkey and were probably attributable to differences between studies in sample size, farms and regions (Avanus and Altınel, 2017). (Lai et al, 2017).…”
Section: Resultssupporting
confidence: 87%
“…It was also lower than that reported by previous Taiwanese studies, in which 409, 172 and 436 cattle from 4, 4 and 9 herds, respectively, with BY carrier frequencies of 8.56, 12.21 and 6.65%, respectively, were sampled (Liaw et al, 2015;2017;Lai et al, 2017). The variations in carrier prevalence were consistent with those found in a study in Turkey and were probably attributable to differences between studies in sample size, farms and regions (Avanus and Altınel, 2017). (Lai et al, 2017).…”
Section: Resultssupporting
confidence: 87%
“…Gaur et al (2012), found a few carriers in Indian Holstein population. Incidence of citrullinemia was altogether absent in Turkish Holsteins as reported by Agaoglu et al (2015) and Avanus and Altinel (2017). Branda et al (2016), carried out PCR-RFLP for detection of citrullinemia in Uruguay where no carrier was detected among the study population (n=190).…”
Section: Discussionmentioning
confidence: 77%
“…Magotra et al, 2020 to screen breeding sires for genetic diseases in order to avoid an unnecessary spread within the population (Meydan et al, 2010). There are several genetic disorders reported in Holstein and Holstein crosses that affect performance traits, physiological functions and the surviability of calves (Avanus and Altinel, 2017). These include bovine leukocyte adhesion deficiency (BLAD), factor XI deficiency (FXID), bovine citrullinemia (BC) and deficiency of uridine monophosphate synthase (DUMPS) that leads to significant economic losses (Gholap et al, 2014;Morkuniene et al, 2019;Marron et al, 2004;Ramesha et al, 2017b).…”
Section: Article Historymentioning
confidence: 99%